L'alimentation des esclaves d'origine africaine de la Basse-Louisiane française (1724-1751) : une fenêtre sur les rapports de pouvoir dans une société de frontière esclavagiste - Jacques-Côté, Ariane (Université de Montréal, 2011)
By studying practices related to slave food in French Louisiana, we learn more about solidarities and conflicts between social groups and within these groups in a slave frontier society. The first chapter is about two main strategies of whites related to slave food: to preserve the slave population and to control their participation in the economy. The second chapter is about the roles of slaves in the food economy, as specialized workers and as producers and distributors of food; these roles enable them to gain more autonomy within the colonial society. The different strategies of slaves in the area of food are at the heart of conflicts and of solidarity between them.
Keywords: Alimentation; Esclavage; Food; History - United States / Histoire - États-Unis (UMI : 0337); Louisiana; Louisiane; Slavery